Relationship between Hyperglycemia and Outcome of COVID-19 Patients - Anna Andriana; Karel Pandelaki; Linda W. A. Rotty (Universitas Sam Ratulangi, 2022)
Abstract: Diabetes is one of the most common diseases found in COVID-19 patients. People with diabetes have a higher risk of developing a more severe form when infected with the SARS-CoV2 virus. This study aimed to determine the relationship of hyperglycemia and the outcome of COVID-19 patients. This was a literature review study using three databases, namely Pubmed, ClinicalKey, and Google Scholar. The outcomes studied were the degree of COVID-19 disease and the mortality rate of COVID-19 patients. The results obtained 10 articles that met the inclusion and exclusion criteria. COVID-19 patients suffering from hyperglycemia, both those with and without a history of diabetes, experienced more severe degree of illness and higher mortality rate compared to patients without hyperglycemia. In conclusion, there is a relationship between hyperglycemia and the severity of illness and mortality in COVID-19 patients.Keywords: hyperglycemia; COVID-19Â Abstrak: Diabetes melitus (DM) merupakan salah satu penyakit yang paling sering ditemukan pada pasien COVID-19. Penyandang DM berisiko lebih tinggi untuk berkembang menjadi bentuk yang lebih parah ketika terinfeksi virus SARS-CoV2. Penelitian ini bertujuan untuk mengetahui hubungan hiperglikemia dengan luaran pasien COVID-19. Jenis penelitian berbentuk literature review dengan pencarian data menggunakan tiga database yaitu Pubmed, ClinicalKey,dan Google Scholar. Luaran yang diteliti yaitu derajat penyakit dan angka kematian pasien COVID-19 dengan DM. Hasil penelitian mendapatkan 10 artikel yang memenuhi kriteria inklusi dan ekslusi. Pasien COVID-19 dengan hiperglikemia baik yang penyandang DM maupun tanpa riwayat DM mengalami keparahan penyakit yang lebih berat dengan angka kematian yang lebih tinggi dibanding pasien tanpa hiperglikemia. Simpulan penelitian ini ialah terdapat hubungan antara hiperglikemia dengan keparahan penyakit dan angka kematian pasien COVID-19.Kata kunci: hiperglikemia; COVID-19